Recent Advances and Future Directions in Sonodynamic Therapy for Cancer Treatment - Priyankan Datta; Sreejesh Moolayadukkam; Dhrubajyoti Chowdhury; Adnan Rayes; Nan Sook Lee; Rakesh P. Sahu; Qifa Zhou; Ishwar K. Puri (BME Frontiers)
Deep-tissue solid cancer treatment has a poor prognosis, resulting in a very low 5-year patient survival rate. The primary challenges facing solid tumor therapies are accessibility, incomplete surgical removal of tumor tissue, the resistance of the hypoxic and heterogeneous tumor microenvironment to chemotherapy and radiation, and suffering caused by off-target toxicities. Here, sonodynamic therapy (SDT) is an evolving therapeutic approach that uses low-intensity ultrasound to target deep-tissue solid tumors. The ability of ultrasound to deliver energy safely and precisely into small deep-tissue (>10 cm) volumes makes SDT more effective than conventional photodynamic therapy. While SDT is currently in phase 1/2 clinical trials for glioblastoma multiforme, its use for other solid cancer treatments, such as breast, pancreatic, liver, and prostate cancer, is still in the preclinical stage, with further investigation required to improve its therapeutic efficacy. This review, therefore, focuses on recent advances in SDT cancer treatments. We describe the interaction between ultrasound and sonosensitizer molecules and the associated energy transfer mechanism to malignant cells, which plays a central role in SDT-mediated cell death. Different sensitizers used in clinical and preclinical trials of various cancer treatments are listed, and the critical ultrasound parameters for SDT are reviewed. We also discuss approaches to improve the efficacies of these sonosensitizers, the role of the 3-dimensional spheroid in vitro investigations, ultrasound-controlled CAR-T cell and SDT-based multimodal therapy, and machine learning for sonosensitizer optimization, which could facilitate clinical translation of SDT.